The cultural context of training: the case of the interpreter in China and Australia - Guo, Ning; Muurlink, Olav; Doyle, Shane (Frontiers in Education, 2023)
China and Australia differ markedly in cultural and social context, the demands placed on interpreters, and the training provided to interpreters to prepare them for professional duties. This paper aims to explore China and Australia’s translation and interpreting (T&I) training programs to elaborate on the ‘goodness of fit’ of training and demonstrates how both the pragmatic and cultural context of interpreting (in both nations) explains anomalies in their training approaches.